The association between alcohol use disorder and suicidal ideation in a New Zealand birth cohort. (December 2022) - Crossin, Rose; Cleland, Lana; McLeod, Geraldine FH; Beautrais, Annette; Witt, Katrina; Boden, Joseph M
Background: Alcohol use disorder is associated with increased suicide risk; however, both alcohol use disorder and suicide share risk factors which must be accounted for in order to understand this relationship. This study aimed to explore the longitudinal relationship between alcohol use disorder and suicidal ideation in adulthood, while accounting for both child background and adult covariate factors. Method: Data were collected from the Christchurch Health and Development Study, a birth cohort of 1265 children born in Christchurch (New Zealand) in mid-1977. Alcohol use disorder (operationalised as alcohol abuse and alcohol dependence) was quantified between age 18 and 40 in five data waves. The outcome measure suicidal ideation was reported over the same time periods. Childhood confounding variables were controlled for, as well as time-dynamic covariates collected in adulthood, including internalising disorders, distress due to relationship dissolutions and other substance use disorders. Results: The association between alcohol abuse and suicidal ideation was not statistically significant before or after adjusting for childhood confounding and adulthood covariate factors, when compared to no alcohol disorder. However, the association between alcohol dependence and suicidal ideation was significant both before and after adjustment (unadjusted odds ratio = 2.89, 95% confidence interval = [2.09, 3.99]; adjusted odds ratio = 1.52, 95% confidence interval = [1.04, 2.23]), when compared to no alcohol disorder. Furthermore, alcohol dependence remained significant when compared to alcohol abuse (unadjusted odds ratio = 2.33, 95% confidence interval = [1.61, 3.37]; adjusted odds ratio = 1.54, 95% confidence interval = [1.00, 2.37]). Conclusion: This analysis found an association between alcohol dependence and suicidal ideation within a New Zealand birth cohort, which persists even after adjustment for childhood confounding and adulthood covariate factors. Given the high rates of suicide and heavy drinking within the New Zealand population, any comprehensive national or regional suicide prevention plan should seek to reduce risky alcohol consumption at an individual and population level, as this represents a modifiable risk factor for suicide.